Midwifery Health Service Booking Information System Based on Progressive Web App at Bidan Care Clinic - Inayah, Nur; Maulana, Reza; Ibrahim, Firmansyah; Rahman (Prodi Sistem Informasi UIN Alauddin, 2023)
Bidan Care Clinic is a health service that provides homecare services in the field of midwifery health. The problem that exists at the Bidan Care Clinic today is the process of ordering homecare services that still use whatsapp, so it is considered still inefficient, because the process of ordering homecare services through the whatsapp application requires communication or feedback between midwives and prospective patients to get information about ordering homecare services. This study aims to design and build a midwifery health service booking information system based on progressive web Application (PWA) at the Bidan Care Clinic. The system built was developed based on PWA because it has several advantages such as a responsive display, automatic update process, can be added to the home screen page without an installation process, the push notification feature and can be accessed again even in offline internet conditions. The system development method used is using the Rapid Application Development (RAD) method and system testing using the Blackbox and System Usability Scale (SUS) methods. Based on the results of SUS testing that has been done, it shows a result of 80.32 or gets an adjective rating of